The Common Good: Collaborative Corporate Citizenship - Lang, Josephine Chinying (Advances in Social Sciences Research Journal, 2023)
I propose a model of emergent collaborative corporate citizenship (CCC) in which organizations jointly develop dynamic capabilities to address social and environmental concerns through collaborative sense-making and collaborative actions. Using a complexity science framework, I describe how the system conditions of organizational diversity and an economy of interdependence enhance the capability for organizing around responses to social and environmental imperatives. Inter-organizational collective actions magnify and intensify how organizations modify their strategies to incorporate social and environmental considerations. As organizations collaboratively modify their sense-making mechanisms, amend their decision criteria, and adapt their operational routines to incorporate social and environmental responsiveness, the larger business system is thereby changed.